THE DYNAMICS OF INDIAN OCEAN DURING INDIAN OCEAN DIPOLE (IOD) EVENTS 1993â2016 - Bagas Hatmaja, Rahaden
Indian Ocean Dipole (IOD) is an interannual dipole mode phenomenon in the Indian Ocean which is charaterized by the different sea surface temperature (SST) anomaly in the southeastern Indian Ocean and western Indian Ocean, and also accompanied by wind and rainfall anomaly. In this research, Empirical Orthogonal Function (EOF) method is conducted to assess the dynamics of Indian Ocean characteristics, (i.e. sea surface temperature (SST) anomaly, sea surface height (SSH) anomaly, and surface wind), as the response of IOD independently or ignoring the influence of other phenomena (e.g. El–Niño Southern Oscillation (ENSO), monsoon, etc). Based on the EOF analysis, IOD explains about 19,6% of the total variation of interannual SST anomaly (EOF second mode) for last 24 years. While due to the others parameters, IOD explains about 41,6% of the total SSH anomaly variation (EOF first mode), 53,5% of the total anomalous zonal wind variation (EOF first mode), and 21,8% of the total anomalous meridional wind variation (EOF second mode). Based on the EOF analysis and also temporal dan spatial cross correlation analysis, it's obtained some accurate indice and able to describe the dynamics of Indian Ocean during IOD events, such as SSTdyn (for SST anomaly dynamics), Udyn (for zonal wind anomaly dynamics), Vdyn (for meridional anomaly dynamics), and SSHdyn (for SSH anomaly dynamics). Moreover, based on the composite analysis of the EOF analysis (Principal Component or PC) and Indian Ocean dynamics indices, during the positive (negative) IOD events in 1994, 1997, 2006, 2012, and 2015 (1996, 1998, 2010, and 2016), the negative (positive) SST anomaly in the eastern Indian Ocean (0°–10°S dan 90°–110°E) followed by the positive (negative) SST anomaly in the western Indian Ocean (10°N–10°S dan 40°–60°E) and the central Indian Ocean (5°S–10°S dan 70°–80°E) occur in June and reach the peak in September-October. The anomalous SST is also accompanied by anomalous wind in the region of 5°N–10°S dan 70°–110°E, which starts by the occurance of anomalous northerlies (southerlies) meridional wind in June-July, continues by the occurance of anomalous easterlies (westerlies) zonal wind in the following month, and reaches the peak in October. Moreover, the anomalous SSH also occurs due to the anomalous wind. The positive (negative) SSH anomaly in the central Indian Ocean (5°S–10°S and 60°–90°E) and the negative (positive) SSH anomaly in the eastern Indian Ocean (5°N–10°S and 90°–110°E), occur in July-August (September-October) and reach the peak in November-December (January).